2019
DOI: 10.3390/f10090809
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Pattern of Climate Change Effects on Lithuanian Forestry

Abstract: Research Highlights: Validating modelling approach which combines global framework conditions in the form of climate and policy scenarios with the use of forest decision support system to assess climate change impacts on the sustainability of forest management. Background and Objectives: Forests and forestry have been confirmed to be sensitive to climate. On the other hand, human efforts to mitigate climate change influence forests and forest management. To facilitate the evaluation of future sustainability of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 54 publications
(80 reference statements)
2
9
0
Order By: Relevance
“…Determining the exact impact of external factors on ES indicators by comparing scenarios is difficult. Forest management in the scenarios differed as a response to the external factors and the largest impact on ESs was the level of clearfelling in the scenarios, which was mainly determined by the dynamic timber prices (Lundholm et al, 2019), a finding also confirmed using the same global scenario narratives in Lithuania (Mozgeris et al, 2019). Some correlations were found, where the greatest clearfell area (in the S3 scenario) resulted in more P emissions (which reduced water quality), and reductions in the area at windthrow risk, cumulative carbon storage, biodiversity indicators and RAFL-index.…”
Section: External Impacts and Forest Compositionsupporting
confidence: 53%
See 1 more Smart Citation
“…Determining the exact impact of external factors on ES indicators by comparing scenarios is difficult. Forest management in the scenarios differed as a response to the external factors and the largest impact on ESs was the level of clearfelling in the scenarios, which was mainly determined by the dynamic timber prices (Lundholm et al, 2019), a finding also confirmed using the same global scenario narratives in Lithuania (Mozgeris et al, 2019). Some correlations were found, where the greatest clearfell area (in the S3 scenario) resulted in more P emissions (which reduced water quality), and reductions in the area at windthrow risk, cumulative carbon storage, biodiversity indicators and RAFL-index.…”
Section: External Impacts and Forest Compositionsupporting
confidence: 53%
“…Analyzing the long-term impacts of various global development scenarios on forest management approaches and forest ESs is crucial to avoid negative outcomes and conflicts between stakeholders. The ALTERFOR project is a collaboration between 9 countries (Germany, Ireland, Italy, Lithuania, The Netherlands, Portugal, Slovakia, Sweden, and Turkey; Marques et al, 2017;Marto et al, 2018;Schwaiger et al, 2018Schwaiger et al, , 2019Mozgeris et al, 2019;Nordström et al, 2019) that investigates the suitability of FMDSSs to analyse the complex dynamic interactions between climate change, global markets, and forest management practices to assess the suitability of current and alternative forest management systems to address future challenges and provide society with an optimal mix of ESs. Standardized ES indicators have been implemented in nine different FMDSSs to allow for comparisons across European landscapes and facilitated the large-scale analysis of long-term climate change and bioeconomy impacts on the provision of forest ESs in Europe (Nordström et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…These countries are the main producers of raw timber, as well as large importers of harvested timber from the Czech Republic. The price of spruce wood thus depends not only on the volume of mining, but also on the technological capacities of the processing countries [35][36][37]. The technological capacities of Austria and Germany are close to 100%; therefore, further development depends on the ability and willingness of these countries to harvest raw timber in the Czech Republic.…”
Section: Discussionmentioning
confidence: 99%
“…Mozgeris et al [21] investigated climate change and its impacts on the sustainability of forest management (forest growth, global timber demands and prices) in a Lithuanian forest ecosystem with three climate change scenarios using an in-house forest simulator called Kupolis. Because the case study area is in the Northern hemisphere, a warmer climate change effect is found to increase tree size, stand productivity, and growing stock, resulting in higher profits yet negative dynamics of biodiversity (decrease broadleaf cover and tree species diversity).…”
Section: Case Studies With Simulation and Scenario Analysismentioning
confidence: 99%